Aminoglycoside antibiotic kanamycin functionalized tetraphenylethylene molecular probe for highly selective detection of bovine serum albumin protein - Ratan W. Jadhav; Sopan M. Wagalgave; Bajarang V. kumbhar; Rushikesh M. Khadake; Ambadas B. Rode; Sidhanath V. Bhosale; Sheshanath V. Bhosale (Scientific Reports, 2022)
Abstract A novel tetraphenylethylene (TPE) functionalized aminoglycoside antibiotic kanamycin (TPE-kana 1) has been successfully synthesized and characterized by means of modern analytical and spectroscopic techniques. The probe TPE-kana 1 showed strong affinity towards bovine serum albumin (BSA) compared to its other biological competitors. The recognition of BSA have been investigated employing UV–Vis absorption and fluorescence emission spectroscopy. The significant color change of TPE-kana 1 with BSA can be observed by necked eye, where the role of AIE-active TPE molecule is handle in both optical and colorimetric changes. The quenching of fluorescence of TPE-kana 1 with BSA was characterized by fluorescence spectroscopy, with 71.16% of quenching efficiency. Moreover, the Stern–Volmer quenching constant was calculated and found to be 2.46 × 107 M−1. Probe TPE-kana 1 showed detection limit of 2.87 nM (nM) towards BSA with binding constant 7.56 × 107 M. A molecular docking study is also performed to investigate the detail interactions between TPE-kana 1 with the sites of BSA via non-covalent i.e., H-bonding, π-cation interactions, π-donor hydrogen bonds and π-π interactions. The lowest binding energy conformation was found at − 10.42 kcal/mol.